Pengaruh Inflasi, Profitabilitas, dan Tingkat Suku Bunga Terhadap Harga Saham Perusahaan LQ45 Periode 2019 - 2023 - Ramadhan, Aditya; Zulkarnain, Iskandar (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to determine the effect of inflation, profitability, and interest rates on stock prices of LQ45 companies for the period 2019–2023. This study uses an associative quantitative design to test the effect of inflation, profitability (ROA), and interest rates on stock prices of LQ45 companies with secondary data from the IDX and Stockbit, involving 11 sample companies during 2019–2023. Data analysis was carried out using panel data regression with classical assumption tests, as well as t-tests and F-tests to measure the partial and simultaneous effects of independent variables on stock prices. The test results are intended to evaluate the strength and direction of the relationship between independent variables and stock prices, with the coefficient of determination (R²) as an indicator of variable contribution. The results show that inflation and profitability have a negative and insignificant effect on stock prices, while interest rates have a positive and significant effect. Simultaneously, these three variables have a positive and significant effect on stock prices of LQ45 companies.